Mapping the Intellectual Landscape of Sustainable Finance: A Bibliometric Analysis - Loso Judijanto (North Press, 2025)
This study presents a comprehensive bibliometric analysis of the evolving field of sustainable finance, aiming to map its intellectual structure, thematic trends, and collaborative networks. Drawing on a dataset of scholarly publications indexed in the Scopus database from 2000 to 2024, the study employs VOSviewer to conduct co-authorship, country collaboration, keyword co-occurrence, temporal overlay, and density visualizations. The analysis identifies